THE INTEGRATION OF ISLAMIC VALUES IN IMPLEMENTATION OF LEARNING ENGLISH: ISLAMIC EDUCATION STUDENTS PERSPECTIVE - Mochlis Eko Wijayanto (Universitas Islam Negeri Alauddin Makassar, 2020)
The learning process at the University of Nurul Jadid must be guided by Trilogi Santri and Panca Kesadaran Santri formulated by the founder of the Nurul Jadid Islamic Boarding School Foundation. Thus, each learning program at the Faculty of Islamic Religion (FAI) of Nurul Jadid University must be able to produce teachers who can integrate Islamic values in their teaching, including learning English itself. To find out students as prospective teachers of Islamic religious education are able to integrate Islamic values into learning English. The problem in this research is,